2012
DOI: 10.1055/s-0032-1315961
|View full text |Cite
|
Sign up to set email alerts
|

Quality Standards for Sample Collection in Coagulation Testing

Abstract: Preanalytical activities, especially those directly connected with blood sample collection and handling, are the most vulnerable steps throughout the testing process. The receipt of unsuitable samples is commonplace in laboratory practice and represents a serious problem, given the reliability of test results can be adversely compromised following analysis of these specimens. The basic criteria for an appropriate and safe venipuncture are nearly identical to those used for collecting blood for clinical chemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 162 publications
(152 citation statements)
references
References 74 publications
1
135
0
16
Order By: Relevance
“…Commercial tubes have multiple components that contribute to the optimal separation of serum or plasma for laboratory analysis. For example, in glass blood collection tubes, the glass interior surface itself plays a key role in the activation of blood coagulation [28] . Recent use of plastic, as the principal material of collection tubes, has required the addition of silica particles or other clot activators for optimal formation of serum.…”
Section: Blood Collection Tube Interference On Clinical Chemistry Assaysmentioning
confidence: 99%
“…Commercial tubes have multiple components that contribute to the optimal separation of serum or plasma for laboratory analysis. For example, in glass blood collection tubes, the glass interior surface itself plays a key role in the activation of blood coagulation [28] . Recent use of plastic, as the principal material of collection tubes, has required the addition of silica particles or other clot activators for optimal formation of serum.…”
Section: Blood Collection Tube Interference On Clinical Chemistry Assaysmentioning
confidence: 99%
“…The most prevalent pre-analytical errors are those occurring during the collection of blood specimens; so the definition, implementation, and monitoring of suitable sample collection standards are highly conducive to improving the quality of the testing process [ 50 ]. In particular, harmonization projects should adhere to standardized protocols for patient preparation, time and use of appropriate devices and techniques for sample collection.…”
Section: Sample Collection and Handlingmentioning
confidence: 99%
“…Presently in order to start a ''light-side'' period in the preanalytical phase and in patient safety, the attention of the laboratory professionals has been focused on some procedures previously regarded as consolidated, such as: (i) furniture changes among different manufacturers of syringes for blood gas analyses, which can represent new sources of laboratory variability; similar considerations apply to not validated vacuum tubes [28][29][30][31]; (ii) transport boxes unable to guarantee the maintenance of the temperature during blood specimens transportation [32]; (iii) traditionally accepted although incorrect paradigms ranging from the filling of vacuum tubes to the mixing procedures which appear unsupported by accurate experimental verification; e.g., recently it has been observed that there is no apparent need to mix all blood specimens after collection into vacuum tube systems by venipuncture [33,34]. On the other hand, apparently incorrect vigorous mixing of the primary blood vacuum tubes immediately after collection does not promote laboratory variability [35]; more so, no clinical impact has been observed in routine and specialized coagulation laboratory testing when the vacuum tubes are incompletely filled (when filled more than 90 % but \100 %) [36]. Obviously the ability of the phlebotomist to put the patient at ease is considered very important by outpatient [37].…”
Section: Discussionmentioning
confidence: 99%